The Prevalence of Needle Stick Injuries among Dental Students, University of Benghazi, Libya - Beaayou, Hawwa S (Scientific Journal of University of Benghazi, 2020)
Introduction: Dentists and dental students are at high risk of injuries by sharps and of these, the most common are due to needle sticks. Needle-Stick Injures (NSIs) increase the risk of having blood-borne infections such as Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), and Human Immunodeficiency Virus (HIV) infections. Aims: The aim of this study was to determine the prevalence and pattern of (NSIs) among dental students at Faculty of Dentistry, Benghazi – Libya. Methods: A descriptive cross sectional study was conducted among all dental students who were in clinical rotations (third year, fourth year and interns) at Faculty of Dentistry, University of Benghazi. Students were surveyed for the prevalence and pattern of (NSIs) using a pre-tested, self-administered questionnaire. The data was collected and analyzed by using SPSS software. Results: About one third of the students had at least one accidental exposure to (NSIs) since the beginning of their dental training. Needle Recapping was the most common cause of such injury. Most of dental students (73.3%) were found to be aware of precautionary measures and first aid management for a (NSIs). Conclusion and Recommendations: Proper training system, proper work practices and education regarding awareness of needle stick injuries have the prime importance of creating awareness. The prevention and management protocol for such injury should be displayed in all clinical departments to assure safe practicing. HBV vaccination should be strongly recommended for all dental students before beginning clinical rotations to reduce the risk of HBV infections through needle stick injury.